Origins of food crops connect countries worldwide - Khoury, Colin K.; Achicanoy Estrella, Harold Armando; Bjorkman, Anne D.; Navarro Racines, Carlos Eduardo; Guarino, Luigi; Flores Palacios, Ximena; Engels, Johannes M.M.; Wiersema, John H.; Dempewolf, Hannes; Sotelo, Steven; Ramírez Villegas, Julián Armando; Castañeda Álvarez, Nora P.; et al. (Royal Society, 2016)
Research into the origins of food plants has led to the recognition that specific geographical regions around the world have been of particular importance to the development of agricultural crops. Yet the relative contributions of these different regions in the context of current food systems have not been quantified. Here we determine the origins (‘primary regions of diversity’) of the crops comprising the food supplies and agricultural production of countries worldwide. We estimate the degree to which countries use crops from regions of diversity other than their own (‘foreign crops’), and quantify changes in this usage over the past 50 years. Countries are highly interconnected with regard to primary regions of diversity of the crops they cultivate and/or consume. Foreign crops are extensively used in food supplies (68.7% of national food supplies as a global mean are derived from foreign crops) and production systems (69.3% of crops grown are foreign). Foreign crop usage has increased significantly over the past 50 years, including in countries with high indigenous crop diversity. The results provide a novel perspective on the ongoing globalization of food systems worldwide, and bolster evidence for the importance of international collaboration on genetic resource conservation and exchange.